Clinical Response To Switch From Ranibizumab To Aflibercept In Wet Age-Related Macular Degeneration - Bhagya Weerasinghe; Chandni Gupta; Yasmin Levene; Jai Shankar (Delhi Journal of Ophthalmology)
Introduction: To assess whether switching from Ranibizumab to Aflibercept conferred benefit in visual acuity (VA) and central macular thickness (CMT) in patients with wet age-related macular degeneration (AMD). Methods: Mean change in VA and CMT was assessed in wet AMD patients 6 months prior and 6 months after switch from Ranibizumab to Aflibercept, between July 2014 and November 2016. Results: 90 eyes were switched from Ranibizumab to Aflibercept. VA improved in 11 eyes, 65 reported no change and 14 showed deterioration. Improvement in VA was not statistically significant (p>0.05). CMT improved in 24 eyes, 64 showed no change and in 2 there was deterioration. This improvement was statistically significant (p<0.01). Sub-analysis into patients that had switched to Aflibercept after 6 (28 patients) or >6 (62 patients) Ranibizumab injections showed no significant difference between these groups for VA or CMT change. Conclusion: Although there seemed to be an improvement in the CMT with Aflibercept, this did not translate as a statistical improvement in VA. Switching earlier to Aflibercept did not show any significant benefit in either VA or reduced CMT within the first 6 months. Our research however, requires extension as the benefits may be seen over a longer period of time. In conclusion, some patients with sub-optimal response to Ranibizumab may benefit from switching to Aflibercept.